O estado brasileiro e a política pública de desenvolvimento territorial - CRUZ, Danilo Uzêda da (2014)
This study aims to analyze the public policy of Territorial Development underway in Brazil, its structure and functioning. For that we used as a criterion for analyzing the theoretical concepts around which now rests, sometimes conflicts such development strategy, namely the state and liberal democracy as a backdrop and the practice of territorial development. Through theoretical analysis, supported by discussion of the theories of the capitalist state, the paradigms of development in Latin America and Brazil, and in the analysis of the formulation of territorial development policy, we seek to characterize the public policy of territorial development, and their theoretical frameworks and , operating. Thus we hypothesized for the concrete fact, the shortcomings of public territorial development policy to promote the development proposed by its own internal contradiction in not considering how experienced critical economic, social, political, environmental and cultural issues by populations in the territories. Official documents, decrees and institutional literature were analyzed, and the operation of institutional spaces for participation created from the territorial development policy, considering the minutes and bylaws of the board of participatory monitoring of multi-year plan and the state board of territorial development. The prospect that the policy operated as the state apparatus, in the formulation of public policy on territorial development, if the block of hegemonic power, present in the state bureaucracy. The possibilities of inserting demands on the political system from the participation of these public spaces are limited to the bureaucratic structure of the state, affecting the functioning of the same public policy itself.